The Multiple Benefits of Urban Green-Ecosystem Services Assessment - Grunewald, Karsten; Xie, Gaodi; Wüstemann, Henry (Springer, 2018)
The elements of the green infrastructure in the urban space represent habitats for numerous species and provide a high variety of ecosystem services. A clarification of the benefits urban residents gain from urban green spaces as well as control of urban green quality at the city and federal level are necessary to derive and pinpoint urban planning and nature conservation strategies in this context. In this light, due to its integrated approach the concept of ecosystem services (ES) is gaining increased popularity in the global environmental debate.
Keywords: Stadtentwicklung; Ökologie; Nachhaltige Entwicklung; Landschaftsverbrauch; Flächennutzung; Stadtgrün; Wirkung; Stadtökologie; Stadtnatur; Biodiversität; Ökosystem; Lebenszufriedenheit; Gesundheit; Umweltschutz